USE OF AUDIO VISUAL AIDS (AVA) MEDIA BASED ON CHILDREN'S LEARNING STYLE IN WRITING CONCLUSIONS IN CLASS VI SDN 40 BANDA ACEH - Nazira, Diva; Safiah, Intan; Fauzi, Fauzi (Universitas Syiah Kuala, 2024)
This research aims to describe the results of writing conclusions using audio visual aids (AVA) media in class VI at SDN 40 Banda Aceh, Academic Year 2023/2024. The method used in this research is a descriptive qualitative method. The data collection technique in this research consists of several things, namely observation, questionnaires and tests. There are five indicators used in the analysis, namely the suitability of the text content to the story, the accuracy of event details, the accuracy of words, the accuracy of sentences, and spelling and writing. The research results showed that students got very good scores on their ability to write conclusions using audio visual aids (AVA) media based on children's learning styles in class VI students at SDN 40 Banda Aceh. This can be seen from the research results in analyzing student data with the lowest score being 75, the highest score being 100, and the average score being 89.5 with a KKM score of 80.